2018
DOI: 10.1245/s10434-018-6384-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Regional Recurrence After Negative Repeat Sentinel Lymph Node Biopsy in Patients with Ipsilateral Breast Tumor Recurrence

Abstract: BackgroundRepeat sentinel lymph node biopsy (rSLNB) has increasingly been used in patients with ipsilateral breast tumor recurrence (IBTR). The safety in terms of regional disease control after this procedure remains unclear. This study evaluates occurrence of regional recurrence as first event in patients with IBTR and negative rSLNB, treated without additional lymph node dissection.Patients and MethodsData were obtained from the Sentinel Node and Recurrent Breast Cancer (SNARB) study. In 201 patients, tumor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In patients with a positive rSLNB, the incidence of an aberrant node being the site of regional metastatic disease is fairly high, at approximately 40% (range 20-72%). [2][3][4] Poodt et al previously reported a low risk of regional recurrence in the setting of a negative SLNB, 5 and herein report a low risk of regional recurrence if lymphatic mapping fails. 1 Importantly, if there is a regional failure, many occur outside the ipsilateral axilla (supraclavicular, internal mammary and contralateral axilla).…”
supporting
confidence: 56%
“…In patients with a positive rSLNB, the incidence of an aberrant node being the site of regional metastatic disease is fairly high, at approximately 40% (range 20-72%). [2][3][4] Poodt et al previously reported a low risk of regional recurrence in the setting of a negative SLNB, 5 and herein report a low risk of regional recurrence if lymphatic mapping fails. 1 Importantly, if there is a regional failure, many occur outside the ipsilateral axilla (supraclavicular, internal mammary and contralateral axilla).…”
supporting
confidence: 56%
“…In a meta‐analysis, the reported false‐negative rate of rSLNB was 4·1 per cent. The clinical ipsilateral recurrence rate after a negative rSLNB was 1·0 per cent after a follow‐up of 5·1 years. Thus, a false‐negative rSLNB seemed to be associated with clinically manifest recurrence in around 25 per cent of patients (1·0 per cent/4·1 per cent × 100).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it was hypothesized that lymph node status determined by rSLNB could have the same role in patients with IBTR. In an earlier study, a low regional relapse rate for rSLNB‐negative patients treated without ALND suggested that omitting ipsilateral ALND was safe, and it was proposed that rSLNB should be adopted as standard of care in IBTR. Going further, the present study analysed the impact of any axillary staging in patients with IBTR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations